Answer
Here are the factorizations of the given expressions:
1. \( x^{3} - 125 = (x - 5)(x^2 + 5x + 25) \)
2. \( x^{3} - x^{2} - 42x = x(x - 7)(x + 6) \)
3. \( \frac{1}{2}x^{3} + 4 = \frac{1}{2}(x + 2)(x^2 - 2x + 4) \)
4. \( \frac{1}{2}x^{2} - 2x + 2 = \frac{1}{2}(x - 2)^2 \)
5. \( 5x^{2} - 3 \frac{1}{5} = \frac{1}{5}(5x - 4)(5x + 4) \)
6. \( y^{4} - 15y^{2} - 16 = (y - 4)(y + 4)(y^{2} + 1) \)
Solution
Sure! Let's factorize each of the given expressions step by step.
---
### 1) \( x^{3} - 125 \)
**Step 1: Recognize the Form**
The expression is a difference of cubes, since \( 125 = 5^3 \).
**Step 2: Apply the Difference of Cubes Formula**
The difference of cubes formula is:
\[ a^3 - b^3 = (a - b)(a^2 + ab + b^2) \]
Here, \( a = x \) and \( b = 5 \).
**Step 3: Substitute into the Formula**
\[ x^3 - 5^3 = (x - 5)(x^2 + x \cdot 5 + 5^2) \]
\[ = (x - 5)(x^2 + 5x + 25) \]
**Final Factorization:**
\[ x^{3} - 125 = (x - 5)(x^2 + 5x + 25) \]
---
### 2) \( x^{3} - x^{2} - 42x \)
**Step 1: Factor Out the Greatest Common Factor (GCF)**
All terms have an \( x \), so factor out \( x \):
\[ x(x^2 - x - 42) \]
**Step 2: Factor the Quadratic**
Factor \( x^2 - x - 42 \).
Find two numbers that multiply to -42 and add to -1. These numbers are -7 and 6.
\[ x^2 - x - 42 = (x - 7)(x + 6) \]
**Final Factorization:**
\[ x^{3} - x^{2} - 42x = x(x - 7)(x + 6) \]
---
### 3) \( \frac{1}{2}x^{3} + 4 \)
**Step 1: Factor Out the GCF**
Factor out \( \frac{1}{2} \):
\[ \frac{1}{2}(x^3 + 8) \]
**Step 2: Recognize the Sum of Cubes**
Notice that \( 8 = 2^3 \).
**Step 3: Apply the Sum of Cubes Formula**
The sum of cubes formula is:
\[ a^3 + b^3 = (a + b)(a^2 - ab + b^2) \]
Here, \( a = x \) and \( b = 2 \).
**Step 4: Substitute into the Formula**
\[ \frac{1}{2}(x^3 + 2^3) = \frac{1}{2}(x + 2)(x^2 - 2x + 4) \]
**Final Factorization:**
\[ \frac{1}{2}x^{3} + 4 = \frac{1}{2}(x + 2)(x^2 - 2x + 4) \]
---
### 4) \( \frac{1}{2}x^{2} - 2x + 2 \)
**Step 1: Factor Out the GCF**
Factor out \( \frac{1}{2} \):
\[ \frac{1}{2}\left( x^2 - 4x + 4 \right) \]
**Step 2: Factor the Quadratic**
Factor \( x^2 - 4x + 4 \).
This is a perfect square trinomial:
\[ x^2 - 4x + 4 = (x - 2)^2 \]
**Final Factorization:**
\[ \frac{1}{2}x^{2} - 2x + 2 = \frac{1}{2}(x - 2)^2 \]
---
### 5) \( 5x^{2} - 3 \frac{1}{5} \)
**Step 1: Simplify the Expression**
First, convert \( 3 \frac{1}{5} \) to an improper fraction:
\[ 3 \frac{1}{5} = \frac{16}{5} \]
So the expression becomes:
\[ 5x^{2} - \frac{16}{5} \]
**Step 2: Factor Out the GCF**
Notice that \( 5x^2 \) and \( \frac{16}{5} \) have a common factor of \( \frac{1}{5} \):
\[ 5x^{2} - \frac{16}{5} = \frac{1}{5}(25x^2 - 16) \]
**Step 3: Recognize the Difference of Squares**
\[ 25x^2 - 16 = (5x)^2 - 4^2 = (5x - 4)(5x + 4) \]
**Final Factorization:**
\[ 5x^{2} - 3 \frac{1}{5} = \frac{1}{5}(5x - 4)(5x + 4) \]
---
### 6) \( y^{4} - 15y^{2} - 16 \)
**Step 1: Let’s Make a Substitution**
Let \( z = y^{2} \). Then the expression becomes:
\[ z^2 - 15z - 16 \]
**Step 2: Factor the Quadratic in \( z \)**
Find two numbers that multiply to -16 and add to -15. These numbers are -16 and 1.
\[ z^2 - 15z - 16 = (z - 16)(z + 1) \]
**Step 3: Substitute Back \( z = y^{2} \)**
\[ (y^{2} - 16)(y^{2} + 1) \]
**Step 4: Factor \( y^{2} - 16 \) Further**
Recognize this as a difference of squares:
\[ y^{2} - 16 = (y - 4)(y + 4) \]
**Final Factorization:**
\[ y^{4} - 15y^{2} - 16 = (y - 4)(y + 4)(y^{2} + 1) \]
---
I hope these step-by-step factorizations help you understand the process better!
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution